Ectopsocidae (Psocodea: ‘Psocoptera’) from Valle del Cauca and NNP Gorgona, Colombia - Manchola, Oscar Fernando Saenz; Obando, Ranulfo González; Aldrete, Alfonso N. García (Zootaxa, 2014)
The results of a survey of the psocid family Ectopsocidae in Valle del Cauca and NNP Gorgona, are here presented. Fifteen species were identified, in the genera Ectopsocus (14 species), and Ectopsocopsis (one species); four of the Ectopsocus species are new to science and are here described and illustrated. The male of E. thorntoni García Aldrete is here described. Records of Ectopsocopsis cryptomeriae (Enderlein), Ectopsocus briggsi McLachlan, E. californicus Banks, E. columbianus Badonnel, E. maindroni Badonnel, E. meridionalis Ribaga, E. pilosus Badonnel, E. richardsi Pearman, E. titschacki Jentsch, and E. vilhenai Badonnel, are provided. Ten species were found only in Valle del Cauca, two species were found only in the NNP Gorgona, and three species were found at both sites. The specimens studied are deposited in the Entomological Museum, Universidad del Valle, Santiago de Cali, Colombia (MUSENUV).